(untitled) (IUBAT Review, 2025)
Finite element modelling is performed in this study for reinforced concrete columns which is subjected to thermal load (fire). Previous experimental studies observed the fire behavior of reinforced concrete columns but no studies observed the fire behaviour of such columns having different cross sections and reinforcement ratios numerically. Fire is applied to the surface of the columns in the form of thermal load. Convection and Radiation has been applied accordingly to the column surfaces. Temperature dependent material properties has been given as input. In this research, numerical analysis is done in ABAQUS software and results are analyzed in terms of fire resistance, maximum temperature developed, temperature contour etc. The fire resistance found using the finite element model demonstrates excellent consistency with standard furnace test outcomes of former research verifying the dependability of the model. Then a parametric study comprised of forty models was performed keeping the principles of verified model same, with varieties of cross sections of column and steel percentages which has produced significant information about the resistance of these types of columns against fire. It is found that bigger column sizes offer more fire resistance in most of the cases whereas higher steel percentages result in less resistance to fire. Results of the parametric study have been compared with existing previous researches. Relationship is established through linear regression analysis between these parameters which is useful while predicting the fire resistance of same type of columns. IUBAT Review—A Multidisciplinary Academic Journal, 8(1): 01-19